2019
DOI: 10.1039/c9ra02450f
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and health risk assessment of volatile organic compounds in the surface water of Poyang Lake in March 2017

Abstract: An investigation into the occurrence of volatile organic compounds (VOCs) in the surface water of Poyang Lake was conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Therefore, TCE is one of the most common chlorine compounds detected in groundwater pollution. Compared to another study during a similar period, the average and maximum concentrations of TCE in Poyang Lake, China were 0.006 and 0.008 µg/L, respectively, with a detection frequency of 18% [38].…”
Section: Overall Distribution Of Voc Concentrationscontrasting
confidence: 57%
See 1 more Smart Citation
“…Therefore, TCE is one of the most common chlorine compounds detected in groundwater pollution. Compared to another study during a similar period, the average and maximum concentrations of TCE in Poyang Lake, China were 0.006 and 0.008 µg/L, respectively, with a detection frequency of 18% [38].…”
Section: Overall Distribution Of Voc Concentrationscontrasting
confidence: 57%
“…Another study covering a similar time period reported that the average and maximum concentrations of chloroform in Dongjiang Lake, China, were 0.22 and 0.28 μg/L, respectively, with a detection frequency of 100% [6]. In Poyang Lake in China, the average and maximum chloroform concentrations were 0.19 and 1.38 μg/L, respectively, with a detection frequency of 100% [38]. Based on these results, we concluded that the most frequently observed VOC concentrations in this study are similar to those observed in China.…”
Section: Overall Distribution Of Voc Concentrationsmentioning
confidence: 92%
“…However, VOCs in the atmosphere are not only soluble in water in their natural state, but also act as pollutants in the aquatic ecosystem, as well as affecting human health. Such VOCs can have negative effects, so it is necessary to also study VOCs in the water environment [12][13][14]17].…”
Section: Literature Review Of Vocs In Watermentioning
confidence: 99%
“…They are included in the category of aesthetic and hazardous organic compounds in the national water quality standard for domestic drinking water in Korea. Thus, pollution caused by VOCs in the water systems has received considerable attention with the advancement of VOC research [13].…”
Section: Introductionmentioning
confidence: 99%
“…With the fast pace in the development and era of modern mechanization the problem of pollution, specifically water pollution has been increased alarmingly in numerous developing countries including India [[11], [12], [13]]. A lot of toxicants in the environment act by damaging of DNA and therefore causing mutations [[14], [15], [16]].…”
Section: Introductionmentioning
confidence: 99%